Implementasi asesmen autentik untuk meningkatkan hasil belajar siswa pada mata pelajaran pendidikan agama Islam - Safuroh, Safuroh; Nugraha, Enung; Wasehudin, Wasehudin; Supardi, Supardi; Hilmiyati, Fitri (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2024)
The implementation of assessment in learning is often suboptimal, particularly in addressing the affective, cognitive, and psychomotor domains comprehensively. Teachers tend to overlook the affective and psychomotor domains, resulting in students demonstrating low competencies in these areas. This study aims to analyze the implementation of authentic assessment to improve student learning outcomes at Madrasah Tsanawiyah Al-Khairiyah Badamusalam. The method employed was Classroom Action Research (CAR) with a descriptive qualitative approach. Data was collected through observation, questionnaires, and documentation. The findings reveal that the planning of authentic assessment achieved a score of 81.2%, the implementation of authentic assessment scored 84.4%, and the student questionnaire results from grade IX indicated a score of 80.2%, all classified as good. Student learning outcomes improved from an average score of 78.4 in cycle I to 85.3 in cycle II, with an increase of 6.9 points. This demonstrates the effectiveness of authentic assessment in enhancing learning outcomes from a moderate to a good category.